Intuitionistic Fuzzy Sets and its Application in Carrier Determination by the Fusion of Score Function and Normalized Hamming Distance Method - Trivedi, Ruchi; Mishra, Vikas Kumar; Dewangan, R. N.; Dewangan, Manoj Kumar; Maheshwari, (Communications in Mathematics and Applications, 2025)
Intuitionistic fuzzy sets are commonly used to solve decision making problems. In this paper, a new score and accuracy function of intuitionistic fuzzy sets have been proposed, and used to solve the carrier determination problems. The fusion of score function and normalized hamming distance method of intuitionistic fuzzy sets have been used to determine the distance between each students and each carrier. The results of this approach were then analyzed to determine the most suitable career paths for each student based on their individual characteristics and preferences.